Quality of life and physical activity seniors with hypertension - Humańska, Marzena Agnieszka; Czapiewski, Łukasz; Ulenberg, Agata; Ulenberg, Grzegorz; Betke, Katarzyna; Felsmann, Mirosława (Journal of Education, Health and Sport, 2019)
Introduction: Hypertension is a very common blood disorder common in older people. This disease, as well as many others that often accompany the elderly, affects both the quality of life and to physical activity of seniors. Aim of the work: To assess quality of life and physical fitness of the elderly. Material and methods: The study was conducted among the elderly in Bydgoszcz. The study used standardized questionnaires such as the scale of the ADL, IADL, Barthel, WHO questionnaire QOL- Bref and Legal Data socjodemgraficznych own authorship. Study on variables was performed using Kruskal-Wallis test and Mann-Whitney test. Variability presented as the arithmetic mean (M) and standard deviation (SD). The level of significance p ≤ 0.05 considered statistically significant. The research group consisted of 100 people. Results: The quality of life of respondents depends on the length of the years of being infected with hypertension. It has been demonstrated statistical relationships in all areas of the WHO scale QOL- Bref, and the period of being infected with hypertension. With the increase in the period of illness reduce the amount of points earned by the respondents, which lowers the quality of life of respondents in every area of the WHO scale QOL- Bref. The length of the ill influence on the physical activity of the test population as assessed by scales: ADL IADL and Barthel. We observed an inverse proportional with the increase where the period of being infected with the disease reduced the results obtained from the questionnaires, indicating a decrease in patient autonomy. Conclusions: We found a statistically significant relationship between the sense of quality of life and the length of years of being infected with hypertension. This observation has any field scale WHOQOL- Bref. Statistical analysis shows that the longer the period of being infected with hypertension, including physical fitness was significantly lower subjects.